CAMEL MODEL ANALYSIS AND DISCRIMINANT ANALYSIS OF COMMERCIAL BANKS’ PERFORMANCE IN GUYANA, SOUTH AMERICA - Raja, Vincent A.; Pasha, Sukrishnalall; Ganapathy, Kumar; Christy, Maria (Indian Journal of Finance and Banking, 2023)
The study evaluates the performance of commercial banks in Guyana using prudential ratios that capture the five essential dimensions of a bank’s operation. It applies the CAMEL rating system and Linear Discriminant Analysis on quarterly prudential ratios of all the commercial banks that operated in Guyana between 2017 and 2021. The CAMEL analysis reveals that Demerara Bank Limited (DBL) is the best-performing bank, and the Guyana Bank for Trade and Industry (GBTI) is the worst-performing bank. However, the one-way ANOVA technique suggests no significant differences between the average values of the prudential ratios in the CAMEL model. Based on the Linear Discriminant Analysis, only four ratios differentiate between good-performing and poor-performing banks. These findings provide valuable insights to regulators that employ these tools to identify poor-performing banks to safeguard the stability and soundness of their domestic banking system. By applying the CAMEL rating system and Linear Discriminant Analysis simultaneously in Guyana, an emerging economy in the Caribbean, for the first time, the study contributes to the literature that utilizes these tools to assess the performance of commercial banks.JEL Classification Codes: G21, G24, L25.